Differentiation of Cerebellum-Type and Parkinson-Type of Multiple System Atrophy by Using Multimodal MRI Parameters - Cui, Bin; Zheng, Weimin; Ren, Shan; Chen, Zhigang; Wang, Zhiqun (Frontiers in Aging Neuroscience, 2021)
Recent studies have demonstrated the structural and functional changes in the multiple system atrophy (MSA) patients. However, little is known about the different parameters changes of the most vulnerable regions in different types of MSA. In this study, we collected resting-state structure, perfusion, and functional magnetic resonance imaging (fMRI) data of cerebellum-type of MSA (MSA-c) and parkinson-type of MSA (MSA-p) patients. First, by simultaneously using voxel-based morphology (VBM), arterial spin labeling (ASL), and amplitude low frequency fluctuation (ALFF), we analyzed the whole brain differences of structure, perfusion and functional activation between the MSA-c and MSA-p patients. Second, we explored the relationships among structure, perfusion, function and the clinical variables in MSA patients. Finally, we extracted the MRI parameters of specific region to separate the two groups and search for a sensitive imaging biomarker. As the results, compared with MSA-p type patients, MSA-c type patients showed decreased structure atrophy in several cerebellum and vermis sub-regions; reduced perfusion in bilateral cerebellum_4_5 and vermis_4_5; as well as decreased ALFF values in right lingual gyrus (LG) and fusiform (FFG). Subsequent analyses revealed the close correlations among structure, perfusion, function, and clinical variables in both MSA-c and MSA-p. Finally, the ROC analysis showed that rCBF of bilateral cerebellum_4_5/ vermis_4_5 could differentiate the two groups at a relatively high accuracy, yielding the sensitivity of 100%, specificity of 79.2%, and the AUC value of 0.936. These findings have important implications for understanding the underlying neurobiology of different types of MSA and added the new evidences for the disrupted rCBF, structure and function of MSA, which may provide the potential biomarker for accurately detecting different types of MSA patients and new ideas for the treatment of different types of MSA in the future.